(untitled) (Journal of Tourism and Himalayan Adventures, 2024)
Mountain ecosystems are experiencing rapid changes in natural environmental conditions and human activities including tourism and development activities. And such factors have substantial impacts on the livelihood of mountain people. Increasing road networks towards the rural settlements have increased the availability of goods and services from the nearby markets, thereby contributing to shifting away from traditional agricultural practices in the rural mountain settlements in Nepal. In this study, we sought to analyze the impact of tourism on agrobiodiversity and livelihood strategies in different villages of Manang with different level of tourist flow; low at Naar, moderate at Ngawal/Khangsar and high at Manang Nysyang. We used semi-quantitative field inventory data to compare diversity on agricultural plant species and livelihood options in these valleys. The study involved 72 households including 16 in Naar village, 26 in Ngawal/Khangsar and 30 in Upper Manang (Nysyang). We have confirmed a total of 60 species of agrobiodiversity in these mountain settlements (excluding microorganisms), with the minimum diversity at Naar Village with 28 species, and with maximum diversity in Upper Manang (51 species). The total number of species under agrobiodiversity is very poor in the mountain settlements of Manang which forms less than 1% of total agricultural species (60/6618) in Nepal. The poor agrobiodiversity in Manang is highly threatened due to various natural and anthropogenic drivers. We believe that our findings will be highly instrumental while making plans and policies for conservation of regional agrobiodiversity in context of changing climate and intensified human activities.